2021
DOI: 10.1111/and.14207
|View full text |Cite
|
Sign up to set email alerts
|

Impact of duloxetine on male fertility: A randomised controlled clinical trial

Abstract: Despite the documented negative impact of some antidepressants on male fertility, an estimated 5.5% of young, fertile men between the ages of 18 and 39 from 2015 to 2018 received an antidepressant medication prescription (Brody 2020;Tanrikut et al., 2010;Tanrikut & Schlegel, 2007). To date, the majority of the studies investigating male infertility have focused on one specific class of antidepressants, selective serotonin reuptake inhibitors (SSRIs) (Beeder & Samplaski, 2020). However, there are numerous other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A recent RCT aimed to investigate differences in DNA fragmentation among 68 healthy males after 6 weeks of treatment with 60 mg Duloxetine or placebo; no significant difference was found between the two groups. Furthermore, semen parameters and serum hormones were not altered by the treatment, showing how Duloxetine, and potentially other SNRIs, may be a good choice for young men desiring to conceive [84].…”
Section: Gonadotoxicity Of Symptomatic and Supporting Therapiesmentioning
confidence: 92%
“…A recent RCT aimed to investigate differences in DNA fragmentation among 68 healthy males after 6 weeks of treatment with 60 mg Duloxetine or placebo; no significant difference was found between the two groups. Furthermore, semen parameters and serum hormones were not altered by the treatment, showing how Duloxetine, and potentially other SNRIs, may be a good choice for young men desiring to conceive [84].…”
Section: Gonadotoxicity Of Symptomatic and Supporting Therapiesmentioning
confidence: 92%
“…There has historically been a paucity of research on the topic, though some in-vitro, animal, and observational studies have shown potential negative effects of selective serotonin reuptake inhibitors (SSRIs) on semen parameters [22]. This negative association was recently called into question by a double-blind placebo-controlled RCT from Cornell, which concluded that administration of duloxetine had no effect on bulk semen parameters [23 ▪▪ ]. These results are encouraging as this is the first adequately powered human study to be published and suggests that at least duloxetine is well tolerated for use in men desiring fertility.…”
Section: Medical Treatmentsmentioning
confidence: 99%